2021
DOI: 10.1111/aas.13977
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation targets in ICU patients with COVID‐19: A post hoc subgroup analysis of the HOT‐ICU trial

Abstract: Background Supplemental oxygen is the key intervention for severe and critical COVID‐19 patients. With the unstable supplies of oxygen in many countries, it is important to define the lowest safe dosage. Methods In spring 2020, 110 COVID‐19 patients were enrolled as part of the Handling Oxygenation Targets in the ICU trial (HOT‐ICU). Patients were allocated within 12 h of ICU admission. Oxygen therapy was titrated to a partial pressure of arterial oxygen (PaO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
(70 reference statements)
0
18
0
Order By: Relevance
“…Based on the data and clinical experience at the beginning of the COVID-19 pandemic in the spring of 2020, 3,17 we expected that 40% of patients would die within 90 days while receiving life support, and survivors would receive an aver-age of 14 days of life support, thus averaging 45.6 days alive without life support for the higher oxygenation group. We estimated that the lower oxygenation target would reduce 90-day mortality by a 20% relative reduction and yield a 10% decrease in days receiving life support for survivors, corresponding to an average of 52.6 days alive without life support in the lower oxygenation group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the data and clinical experience at the beginning of the COVID-19 pandemic in the spring of 2020, 3,17 we expected that 40% of patients would die within 90 days while receiving life support, and survivors would receive an aver-age of 14 days of life support, thus averaging 45.6 days alive without life support for the higher oxygenation group. We estimated that the lower oxygenation target would reduce 90-day mortality by a 20% relative reduction and yield a 10% decrease in days receiving life support for survivors, corresponding to an average of 52.6 days alive without life support in the lower oxygenation group.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 The post hoc subgroup analysis of 110 patients with COVID-19 and acute hypoxemic respiratory failure in the HOT-ICU trial 2 included both mechanically ventilated patients and those treated in open systems, finding that the percentage of days alive without life support was significantly higher when targeting a PaO 2 of 60 mm Hg compared with a PaO 2 of 90 mm Hg, but with no difference in the primary outcome of mortality at 90 days. 3 Establishing a safe oxygenation strategy in COVID-19 patients may ensure that supplemental oxygen is dosed for optimal effect and minimal harm while allowing efficient use of available oxygen supplies, ICU beds, and ventilators. Therefore, the Handling Oxygenation Targets in COVID-19 (HOT-COVID) trial was planned to test the hypothesis that targeting a PaO 2 of 60 mm Hg compared with 90 mm Hg would increase the number of days alive without life support in 90 days in ICU patients with COVID-19 and severe hypoxemia.…”
mentioning
confidence: 99%
“… 9 , 10 A post hoc analysis of the HOT-ICU trial with COVID-19 patients only did not show a statistically significant difference in mortality between a lower and a higher oxygenation target. 14 Conversely, an analysis of the results of 10 trials conducted by the ARDS Network showed that higher oxygen exposure, defined as FiO 2 higher than 0.5 with PaO 2 higher than 80 mmHg was associated with lower ventilator-free days and higher mortality. 15 The reasons for those conflicting results might include different clinical characteristics and severity among included patients, who may have different oxygen demands, and different levels of hyperoxemia that occurred in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several health care systems have been challenged by an increase in oxygen demand due to the outbreak of the severe acute respiratory syndrome coronavirus 2 [ 30 ]. Hence, using a lower oxygenation target in the hypoxaemic patient might help in sparing the available oxygen stockages, and additional interventions such as prone positioning [ 31 ]. The high short-term as well long-term all-cause mortality of our population, which consisted of non-selected hypoxaemic ICU patients, is comparable to that observed in a cohort of mechanically ventilated patients with ARDS [ 2 ], highlighting the disease severity of the trial population.…”
Section: Discussionmentioning
confidence: 99%